Power over pensions? Who should decide and how? - Sixten Korkman (The Research Institute of the Finnish Economy (ETLA), 2009)
The economic profession has widely examined the effects of the pension system on economic efficiency, intergenerational fairness and the sustainability of public finances, while less attention has been paid to the political decision making process. Yet, the essence of the problem is arguably a political bias in decision making in favour of the interests of the present generations. The young and unborn generations may receive little weight by politicians eager to please voters in the next election. The focus in this paper is on decisions on pension entitlements and commitments within the framework of a very simple 'overlapping generations model'. The analysis is first applied to democratic decision making, based on majority voting. In Finland, however, the parliament has devolved much of its power over (earnings-related) pensions to the corporatist system. The democratic and corporatist decision making processes are compared and their relative pros and cons evaluated. The paper also considers the case for refining current decision making structures.
Keywords: 330; Alterssicherung; Gesetzliche Rentenversicherung; Politische Entscheidung; Bias; Demokratie; Korporatismus; Overlapping Generations; Finnland